Aplikasi Pengolahan Report Peternakan Ayam Petelur Berbasis Android - Octa Alief Kiemas Sahid; Yos Richard Beeh (Fakultas Teknologi Informasi Universitas Kristen Satya Wacana, 2022)
In the poultry farm business, there are several activities that require data recording. Generally, data records on the poultry farm business are stored in physical files such as books. Breeders often find it difficult to record changes in the number of chickens in the cage, the number of eggs produced per day, and transactions in the farm. In addition, there is no report system to provide statistics regarding the development of the farm from time to time. The purpose of this research is to build an Android-based application for poultry farms with the aim of helping the breeders in dealing with these problems. The application is built using Android Studio and utilizes SQLite as a database. The notification feature in the application will show a warning at the feeding time. The report feature displays the performance of the farm in a weekly, monthly, or yearly period.